HUBUNGAN PENGETAHUAN TENTANG PERTOLONGAN PERTAMA DENGAN KESIAPSIAGAAN SISWA DALAM SITUASI GEMPA BUMI DI LINGKUNGAN SEKOLAH - I Gusti Ayu Putu Sintya Wulandari; Ni Wayan Suniyadewi; Ni Komang Sukra Andini (Rena Cipta Mandiri, 2026)
SD Negeri 2 Serangan is located in an area with a high risk of earthquakes; therefore, students' disaster preparedness needs to be enhanced through first aid knowledge. This study aimed to analyze the relationship between students' level of first aid knowledge and their preparedness for earthquake disasters. This study employed a descriptive correlational design with a cross-sectional approach. A total of 142 students were selected using a random sampling technique. Data were collected using validated and reliable questionnaires on first aid knowledge and earthquake disaster preparedness. Data were analyzed using Spearman's rank correlation test. The results showed a significant relationship between first aid knowledge and students' earthquake preparedness (p = 0.007; r = 0.227). The correlation coefficient indicated a positive but weak relationship. It can be concluded that higher levels of first aid knowledge are associated with better earthquake preparedness among students. Therefore, continuous first aid education and disaster preparedness training should be implemented to improve students' readiness for earthquake disasters.